Monitoring dan Evaluasi Smart City Kota Surakarta - Budi Winarno; Dwi Sutanto; Wahyu Hermawan; Ibnu Hiban (Jurnal Bengawan Solo Pusat Kajian Penelitian dan Pengembangan Daerah Kota Surakarta, 2023)
The development of technology is now so advanced and rapid. The global era indicates the emergence of a new civilization that brings various conveniences, comforts and welfare of life through the help of information technology devices. Digital civilization is one of the markers of social life between the government, business people and the wider community. Changes in the order of digital-based society include changes in interactions in the world of education which are currently increasingly egalitarian, organizational relationships between non-profit, profit-government which are increasingly in various forms, mass media that utilizes various communication channels, information technology-based governance. , increasing population mobility, an economy based on the industrial revolution 4.0 and the high desire of people to live in a comfortable living atmosphere. This demand was answered by the emergence of the Smart City concept, namely a city that is able to maintain the continuity of the lives of its citizens towards a better quality of life. In this regard, the central government encourages regional governments to develop the Smart City concept in physical and non-physical development in their respective administrative areas which is expected to be able to improve the quality of life of the people who live there.